Mitochondrial DNA mutations can influence the post-implantation development of human mosaic embryos - Ijuin, Akifumi; Ueno, Hiroe; Hayama, Tomonari; Miyai, Shunsuke; Miyakoshi, Ai; Hamada, Haru; Sueyoshi, Sumiko; Tochihara, Shiori; Saito, Marina; Hamanoue, Haruka; Takeshima, Teppei; Yumura, Yasushi; et al. (Frontiers in Cell and Developmental Biology, 2023)
Several healthy euploid births have been reported following the transfer of mosaic embryos, including both euploid and aneuploid blastomeres. This has been attributed to a reduced number of aneuploid cells, as previously reported in mice, but remains poorly explored in humans. We hypothesized that mitochondrial function, one of the most critical factors for embryonic development, can influence human post-implantation embryonic development, including a decrease of aneuploid cells in mosaic embryos. To clarify the role of mitochondrial function, we biopsied multiple parts of each human embryo and observed the remaining embryos under in vitro culture as a model of post-implantation development (n= 27 embryos). Karyotyping, whole mitochondrial DNA (mtDNA) sequencing, and mtDNA copy number assays were performed on all pre- and post-culture samples. The ratio of euploid embryos was significantly enhanced during in vitro culture, whereas the ratio of mosaic embryos was significantly reduced. Furthermore, post-culture euploid and culturable embryos had significantly few mtDNA mutations, although mtDNA copy numbers did not differ. Our results indicate that aneuploid cells decrease in human embryos post-implantation, and mtDNA mutations might induce low mitochondrial function and influence the development of post-implantation embryos with not only aneuploidy but also euploidy. Analyzing the whole mtDNA mutation number may be a novel method for selecting a better mosaic embryo for transfer.